إيجاد الحل الأمثل لنسب التخفيض في ميكانيزمات الروافع بمساعدة الحاسوب - كفا سمير نمر; محمد محمد أحمد (Latakia University Journal -Engineering Sciences Series, 2019)
يضم البحث اقتراحات لحل مشاكل الانتقال من مسألة تحليل التصميمات بمساعدة الحاسوب إلى مسألة إيجاد حلولها المثلى. وهذا الانتقال يمّكن المصمم من استخدام وسائل عصرية وحديثة في أتمتة تصاميم العمل بما فيه رفع نوعية التصاميم المنفذة وجودتها. وانطلاقاً من الواقع العملي لتصميم الآلات الرافعة لوحظ أن سرعتها تؤخذ عادة كمعطيات أولية وقيم هذه السرعات تدخل في لائحة المواصفات التقنية والفنية للآلات الرافعة. في الوقت نفسه فإن شروط الاستثمار تحدد مواصفات وقيم الانتقالات المنفذة وتتابعها المتكرر في دورات إعادة تحميل الروافع. وأخيرا فإنه من الممكن الحصول على اختصار محسوس لاستمرارية الدورة وتخفيض الطاقة المصروفة. The research includes suggestions to move from the issue of design analysis with the aid of the computer to the issue of finding out the optimum solutions. This move enables the designers use modern and up-to-date means in automating the work designs, increasing the quantity of the accomplished designs. Starting from the practical point of view of crane design, it is noticed that velocity is usually taken as a primary reading, and that the values of velocities are included in the technical specifications lists of the cranes. At the same time the investment conditions determine the specifications, the executed mobility values, and their recurrence in the reloading crane cycles. Finally, it is possible to obtain a reasonable deduction in the maintained cycles and to reduce the energy loss.